Loss of consciousness following spinal anaesthesia for caesarean section. - Chan, Y.K.; Gopinathan, R.; Rajendram, R. (Oxford University Press, 2000)
A healthy parturient under spinal anaesthesia for Caesarean section lost consciousness for an hour, 20 min after the intrathecal injection of 2 ml of 0.5% heavy bupivacaine. The patient was haemodynamically stable before losing consciousness. The differential diagnosis is discussed.